The Role of TRPA1 Channels in the Central Processing of Odours Contributing to the Behavioural Responses of Mice - János Konkoly; Viktória Kormos; Balázs Gaszner; Zoltán Sándor; Angéla Kecskés; Ammar Alomari; Alíz Szilágyi; Beatrix Szilágyi; Dóra Zelena; Erika Pintér (MDPI AG, 2021)
Transient receptor potential ankyrin 1 (TRPA1), a nonselective cation channel, contributes to several (patho)physiological processes. Smell loss is an early sign in several neurodegenerative disorders, such as multiple sclerosis, Parkinson's and Alzheimer's diseases; therefore, we focused on its role in olfaction and social behaviour with the aim to reveal its potential therapeutic use. The presence of Trpa1 mRNA was studied along the olfactory tract of mice by combined RNAscope in situ hybridisation and immunohistochemistry. The aversive effects of fox and cat odour were examined in parallel with stress hormone levels. In vitro calcium imaging was applied to test if these substances can directly activate TRPA1 receptors. The role of TRPA1 in social behaviour was investigated by comparing Trpa1 wild-type and knockout mice (KO). Trpa1 mRNA was detected in the olfactory bulb and piriform cortex, while its expression was weak in the olfactory epithelium. Fox, but not cat odour directly activated TRPA1 channels in TRPA1-overexpressing Chinese Hamster Ovary cell lines. Accordingly, KO animals showed less aversion against fox, but not cat odour. The social interest of KO mice was reduced during social habituation-dishabituation and social interaction, but not during resident-intruder tests. TRPA1 may contribute to odour processing at several points of the olfactory tract and may play an important role in shaping the social behaviour of mice. Thus, TRPA1 may influence the development of certain social disorders, serving as a potential drug target in the future.